Ultrastructural morphology of the Myxobolus dermatobius Ishii 1915 (Mixosporea: Myxobolideae) microspores infecting eyes of Nile tilapia (Oreochromis niloticus) in Egypt - El‑Sayed, Nosseur Mohamed (Veterinaria Italiana, 2020)
A total of 1,000 cultured Nile tilapia (Oreochromis niloticus) were collected from different governmental and private fish farms and examined for detection of myxosporean parasites infection. The infected fishes showed slight unilateral exophthalmia with whitish cyst in the eye. Numerous white cysts like plasmodia of Myxobolus dermatobius were recovered from the eye of the examined fishes with low prevalence rate (1%). Small intact cyst was isolated, fixed in 3% glutaraldehyde in 0.1 M sodium cacodylate (pH 7.4) and prepared for transmission electron microscopy examination. Ultrathin sections myxospores of M. dermatobius revealed pair of capsulogenic cells at the apical pole of the developing myxospore. Single sporoplasm containing a single nucleus and sporoplasmosomes fills nearly all the space beneath the polar capsules. The later were pyriform in shape, each one had homogenous dense core and 4 turns of polar filaments. Ultrastructural characteristics of the present myxospore were described and discussed in detail.